A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMPN 1 PUSAKO KABUPATEN SIAK SRI INDRAPURA IN COMPREHENDING RECOUNT TEXTS. - Riptin, Elna; Azhar, Fadly; Ras, Fahri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : The aimed of this research is to know the ability level of the second year students of SMPN 1 Pusako in recount text. The population of this research is the second year students of SMPN 1 Pusako that Consistedof 2 classes; they are VIII 1 (27 students) and VIII 2 (27 students). In this research, the research used purposive sample technique to get the data. All of population is taken as the sample of the research because there were only two classes of eight grade in SMPN1 Pusako. However, the sample of this research consisted of 54 Students. Furthermore, in collecting the data, the students were given the test by the researcher. The test consisted of 40 questions about recount text. The result of this research showed that the mean score in each indicator was 17.08 in finding main idea, 16.85 in finding factual information, 15.69 in finding meaning in difficult word, 16.38 in finding reference questions, and 15.64 in restatement. Based on the mean score of each indicator, the researcher find out the students’ mean score of the students. The mean score of the class VIII students was 81.67 in excellent category. It can be concluded that the second year students of SMPN1 Pusako has excellent category in comprehend the text.Keywords: Reading comprehension, Recount Texts.